RESILIENCE ANALYSIS OF DAYLIGHT PERFORMANCE IN INDONESIAN PUBLIC ELEMENTARY SCHOOL WITH COMPLEX FENESTRATION SYSTEMS CONSIDERING FUTURE CLIMATE CHANGE SCENARIOS - Joyvita Iriani Anthonia, Raynee
Daylight is an important aspect for a classroom as it increases the students’ health and productivity. It also reduces the consumption of energy from the lamps. Indonesia’s public elementary school classroom that is located in tropical area tend to be exposed by the sunlight every year. Some of the factors that effect the daylight performance are the opening design, shading, building orientation. Apart from that, the unpredictable future climate changes may also effect the daylight performance in Indonesia’s public elementary school classroom. To control the enough amount of daylight so it wont cause shortage or excess, a solution in the form of complex fenestration system (CFS) is required to be applied in public elementary school classrooms in Indonesia. This fenestration consists of opening and external shading device. A recent study has produced ten recommendations for optimum CFS design variations for current climate. As a building that will be used for a long period of time, public elementary schools in Indonesia must have a good fenestration design that can maintain daylight performance for many years to come. However, it is unknown whether the optimum design performance can be maintained under future climate scenarios. The daylight performance resilience is defined in this case as a condition of daylight performance that tends to produce a constant value under various climate change scenarios. Modelling and simulation are conducted using Rhinoceros and Grasshopper software. The simulation will be generated based on historical climate data from Climate One Building website and future climate change scenario data from Future Weather Generator. The simulation’s results show that changes in climate data do not cause changes in the performance of daylight in classroom when viewed from the sDA300/50% metric, an increase of 0.3% for ASE1000,250h metric, a decrease of 2.7% for the aUDI100-3000lx metric, and a decrease of 14.5% for the aUDI250-750lx metric. An analysis was then conducted to see the variations of CFS designs that were considered to be the most resilience towards various climate changes for aUDI metrics since it has the most significant value changes. The results of the analysis showed that the CFS designs that were considered the most resilient to all future climate scenarios were designs 1 and 4 for aUDI100-3000lx metric and designs 7 and 10 for aUDI250-750lx metric. Keywords: resilience, classroom, public elementary school, daylighting, future climate change.